2019
DOI: 10.3390/buildings9120243
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Industrial Heritage: Restoration of the Wine Cellar Cooperative in Falset (Catalonia, Spain)

Abstract: Awareness regarding conservation of industrial heritage is recent. Several policies have been adopted to start protecting these buildings because of their historic, artistic and scientific values. Wine cellars are an important example of industrial heritage in Catalonia due to the tradition of this product in the territory and the influence of Art Nouveau and Catalan 'Noucentisme' in their construction and style. The wine cellar in Falset, built by Cèsar Martinell in 1919, has recently been restored and still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several policies have now been adopted to protect these buildings that are in keeping with their historic, artistic, and scientific values. Wine cellars are an important example of industrial heritage in Catalonia due to the area's long winemaking tradition and due to the influence of Art Nouveau and the Catalan 'Noucentisme' in their construction and style [22].…”
Section: The Heritage Of Vernacular Underground Cellars and Other Sig...mentioning
confidence: 99%
“…Several policies have now been adopted to protect these buildings that are in keeping with their historic, artistic, and scientific values. Wine cellars are an important example of industrial heritage in Catalonia due to the area's long winemaking tradition and due to the influence of Art Nouveau and the Catalan 'Noucentisme' in their construction and style [22].…”
Section: The Heritage Of Vernacular Underground Cellars and Other Sig...mentioning
confidence: 99%
“…Western roof trusses are building systems that consist of a triangular frameworkcomprising a series of wood or metal beams properly put together-used to bear the weight of pitched roof tiles. This enables an optimum use of the structure, covering large surfaces at a lower cost than when using beams [30]. Compared with the traditional Chinese-style roof truss, the Western-style triangular roof truss is directly placed on the outer wall without other load-bearing members under it so that the structure can have a larger span and more free space.…”
Section: Architectural Technical Characteristic-two Types Of Roof-tru...mentioning
confidence: 99%
“…Wine and food tourism offers a new way to experience a holiday through the preservation and enhancement of agriculture and wine growing territories. Cuerva et al described a prototypical example of restoration applied to a wine cellar in Spain that was oriented toward cultural tourism [31]. The architectural features of the agro-industrial space were described, and new use was suggested.…”
Section: Introductionmentioning
confidence: 99%